Rheological, Thermodynamic, and Gas Solubility Properties of Phenylacetic Acid‐Based Deep Eutectic Solvents. Issue 4 (15th March 2017) - Altamash, Tausif; Atilhan, Mert; Aliyan, Amal; Ullah, Ruh; Nasser, Mustafa; Aparicio, Santiago
Abstract: Choline chloride + phenylacetic acid‐based deep eutectic solvents are studied. Their most relevant experimental physicochemical properties at different mixing ratios together with the CO2 solubility data obtained in wide pressure and temperature ranges are reported. The presented materials exhibit a significant CO2 capture performance with low corrosion effect when compared with the most common amine‐based CO2 capture agents. Detailed rheological measurements are carried out and various models are applied to describe the dynamic flow behavior of the solvents. The CO2 absorption mechanism is evaluated by studying the behavior of the liquid gas and interface. Due to the advantages of low cost, nontoxicity, and favorable physical properties, these solvents are an environmentally promising alternative for effective CO2 capture technological applications. Abstract : Deep eutectic solvents based on phenylacetic acid show low metal corrosivity and provide suitable physicochemical properties as well as good CO2 solubility. The presented materials exhibit a significant CO2 capture performance as compared to the most common amine‐based agents, thus being promising physical sorbents for carbon capture from power plant flue gases.